플립러닝을 활용한 대학말하기 수업에 대한 인식과 효과성 검토－ 한신대학교 <효과적인 의사소통과 창의적 말하기>를 중심으로 - 송주현 (교양교육연구, 11(5), 2017)
본 연구는 효과적인 학습을 위한 교수방법으로서의 ‘플립러닝(Flipped Learning)’을 한신대 말하기·토론심화 교과인 <효과적인 의사소통과 창의적 말하기>에 적용해 보고 이에 대한 효과성을 구체적인 설문을 통해 점검한다. 통상 ‘거꾸로 학습법’이라고 불리는 플립러닝은 수업의 주체를 학생으로 새롭게 세운다는 점에서 기존의 교수학습 방법에 대한 새로운 관점을 제공한다. 본 연구는 플립러닝에 대한 기존의 부정적 오해를 해소하고 플립러닝의 가치를 구체적인 수업의 내용을 통해 확인한다. 그 결과 교수학습 방법론, 강의실 환경, 의사소통 불안감 해소, 상위인지 활용 및 수업 성취도 면에서 상당한 효과가 있었음을 알 수 있었다. 플립러닝의 교수학습 방법은 수업에 대한 관점의 변화를 추구한다는 점에서 혁신적이다. 그러나 이것이 모든 교수학습방법의 문제점을 해결하는 유일한 해답일 수는 없다. 다만 학생들의 적극적인 참여를 이끌어냄으로써 수업의 주인이 되게하는 의미있는 경험을 마련해 준다는 점, 기존의 교수학습 방법에 대한 새로운 시도이자 도전을 마련해 준다는 점에서 그 의의를 찾을 수 있을 것이다. This study applied ‘Flipped Learning’ as a teaching method for effective learning to ‘Effective Communication and Creative Speaking’, which is a subject for discussion and deepening debate, and examined its effectiveness through specific questionnaires do. Flipped Learning newly establishes the subject of the class as a student. This study solves the existing negative misconceptions about Flipped Learning and confirms the value of Flipped Learning through concrete contents of the lesson. As a result, I have confirmed that I have achieved considerable achievements in terms of teaching-learning methodology, classroom environment, relieving communication anxiety, high cognitive utilization, and class achievement. Flipped Learning is an innovative teaching and learning method. However, this can not be the only solution to the problem of all teaching and learning methods. However, the educational significance can be found in that students are actively involved and lead the class. This change of perspective will be a meaningful starting point for fundamental changes in education. KCI Citation Count: 6